Chronic Tear Deficiency Sensitizes Transient Receptor Potential Vanilloid 1-Mediated Responses in Corneal Sensory Nerves - Masuoka, Takayoshi; Yamashita, Yuka; Nakano, Katsuya; Takechi, Kenshi; Niimura, Takahiro; Tawa, Masashi; He, Qiang; Ishizawa, Keisuke; Ishibashi, Takaharu (Frontiers in Cellular Neuroscience, 2020)
Chronic tear deficiency enhances the excitability of corneal cold-sensitive nerves that detect ocular dryness, which can lead to discomfort in patients with dry eye disease. However, changes in corneal nerve excitations through the polymodal nociceptor “transient receptor potential vanilloid 1” (TRPV1) and the potential link between this receptor and symptoms of dry eye disease remain unclear. In this study, we examined the firing properties of corneal cold-sensitive nerves expressing TRPV1 and possible contributions of chronic tear deficiency to corneal nerve excitability by TRPV1 activation. The bilateral excision of lacrimal glands in guinea pigs decreased the tear volume and increased the frequency of spontaneous eyeblinks 1 to 4 weeks after surgery. An analysis of the firing properties of the cold-sensitive nerves was performed by single-unit recordings of corneal preparations 4 weeks after surgery in both the sham-operated and gland-excised groups. Perfusion of the TRPV1 agonist, capsaicin (1 µM), transiently increased the firing frequency in approximately 46%–48% of the cold-sensitive nerves characterized by low-background activity and high threshold (LB-HT) cold thermoreceptors in both groups. Gland excision significantly decreased the latency of capsaicin-induced firing in cold-sensitive nerves; however, its magnitude was unchanged. Calcium imaging of cultured trigeminal ganglion neurons from both groups showed that intracellular calcium elevation of corneal neurons induced by a low concentration of capsaicin (0.03 µM) was significantly larger in the gland excision group, regardless of responsiveness to cold. An immunohistochemical study of the trigeminal ganglion revealed that gland excision significantly increased the proportion of corneal neurons enclosed by glial fibrillary acidic protein-immunopositive satellite glial cells. Topical application of the TRPV1 antagonist, A784168 (30 µM), on the ocular surface attenuated eye-blink frequency after gland excision. Furthermore, gland excision enhanced blink behavior induced by a low concentration of capsaicin (0.1 µM). These results suggest that chronic tear deficiency sensitizes the TRPV1-mediated response in the corneal LB-HT cold thermoreceptors and cold-insensitive polymodal nociceptors, which may be linked to dry eye discomfort and hyperalgesia resulting from nociceptive stimuli in aqueous-deficient dry eyes.